بر الوالدين في الأغنية الشعبية الجزائرية - وادي سوف أنموذجا - شبرو منانة; عوينات فلة; شرقي جبارية (University of El-oued, 2025)
الملخص: يتمحور موضوع هذه المذكرة حول بر الوالدين في الأغنية الشعبية الجزائرية، فالأغنية الشعبية مرآة تعكس قيم وعادات المجتمع، فهي فن أدبي تناقلته الجماعات الشعبية عن طريق المشافهة وتوارثته الأجيال جيلا بعد جيل وبلهجة عامية يفهمها أفراد المجتمع ويتداولونها في مختلف المناسبات وحتى يمكن التحكم في جمع المادة العلمية تم حصر الموضوع في منطقة وادي سوف، وقد حاولت الدراسة تشخيص الواقع الفعلي لهذا البعد الثقافي المرتبط بالتراث الشعبي الجزائري من حيث المفهوم والنشأة والتطور وكذا الخصائص والأنواع والوظائف..... ومن ناحية أخرى انصرف البحث واتسعت المرحلة التطبيقية للغوص في مكانة الوالدين وبرهما في الأغنية الشعبية بوادي سوف ، ففي البعد الدلالي احتوى لذكر مكانة الأم والأب والبر بهما ، كذلك ذكرت الدراسة أنواع البر وفضله وأثاره في الدنيا والآخرة، كما لا تغفل عن التحدث عن عقوق الوالدين وما ينجر عنها من عواقب وخيمة وهذا باستحضار شواهد من القرآن والسنة ، ونماذج للأغاني الشعبية وتبيان دلالتها من خلال البعد الاجتماعي والبعد الديني في منطقتنا كما تطرقت لدراسة البعد الجمالي لهذه الأغاني من ناحية اللغة والإيقاع والصورة ، مما يساعد في فهم الأغنية الشعبية كعمل فني له قيمة جمالية، بالإضافة إلى المساهمة في تنمية الحس الجمالي لدى المستمعين وتعزيز قدرتهم على تقدير هذا الفن الشعبي. أما فيما يتعلق بالمنهج فقد اعتمدت دراستنا على منهج المقاربة الوصفية بآليات تحليلية متنوعة دلالية وأسلوبية وجمالية بغية التعمق في أغوار الأغنية الشعبية وما تحمله من قيم وجماليات. Abstract: This memorandum focuses on the theme of *filial piety* (respect and care for parents) in Algerian folk songs, specifically in the Oued Souf region. Folk songs serve as a mirror reflecting society's values and customs. They are a literary art form passed down orally through generations, using a vernacular dialect understood and shared by community members on various occasions. To effectively gather research material, the study concentrated on the Oued Souf area. The research aimed to diagnose the actual state of this cultural dimension tied to Algerian folk heritage, examining its concept, origins, evolution, characteristics, types, and functions. Furthermore, the research extended its practical application to delve into the *status of parents and filial piety within Oued Souf folk songs*. Semantically, the study explored the revered position of both mother and father and the importance of honoring them. It also detailed various forms of filial piety, its virtues, and its effects in this life and the afterlife. The study also addressed the serious consequences of *disobedience to parents*, drawing on evidence from the Quran and Sunnah, as well as examples from folk songs to illustrate their social and religious significance in the region. The study also examined the *aesthetic dimension of these songs*, analyzing their language, rhythm, and imagery. This helps in understanding folk songs as artistic works with aesthetic value, contributing to the development of listeners' aesthetic sense and enhancing their appreciation for this popular art form. Regarding methodology, this study adopted a *descriptive approach with diverse analytical tools-semantic, stylistic, and aesthetic-to deeply explore the values and aesthetics embedded within folk songs.
مذكرة .ماستر . أدب شعبي . 2025
Keywords: الأغنية الشعبية بر الوالدين الأبعاد الدلالية، الأبعاد الجمالية; Folk songs; filial piety; Semantic dimensions; Aesthetic dimensions.